Study of Sichuan Art College Students' Usage Behaviour on Digital Libraries under the Background of Digital Intelli-gence - Jie Yu; Jacky Mong Kwan Watt (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study examines the usage behavior of art college students of digital libraries within the context of digital intelligence in Sichuan. It explores how motivational factors, knowledge, and traits influence students' engagement with digital resources. The research highlights that intrinsic motivations, such as personal interest and creativity, significantly drive students to utilize digital libraries effectively. Additionally, the level of digital literacy and familiarity with available resources plays a crucial role in determining usage frequency and depth. Personality traits, such as openness and conscientiousness, also influence how students interact with these platforms. By understanding these dynamics, the study aims to provide insights for educational institutions to enhance digital library services, ultimately fostering better academic outcomes and career readiness for art students in a rapidly evolving digital landscape. The findings suggest that student usage behavior correlates with the influence of motivation, knowledge, and traits in a sample of 385 art college students.